PENGARUH ARUS KAS OPERASI, EARNING PER SHARE (EPS) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Rianita; RM. Rum Hendarmin; Rafika Sari (UNIB Press, 2023)
This study aims to determine the influence of operating cash flow, earnings per share (EPS) and net profit margin (NPM) on the stock price of Food and Beverage companies. The stock price used in this study is the closing stock price for the 2016-2020 period. The population in this study amounted to 32 companies. The sampling technique in this study used purposive sampling with a total sample of 11 companies. The data used is secondary data collected using the documentation method. The analytical technique used is multiple linear regression analysis with SPSS 25 tool. Simultaneous test results show that operating cash flow, earnings per share and net profit margin have an effect on stock prices. The partial test results of operating cash flow have no effect on stock prices, while earnings per share and net profit margin have a positive and significant effect on stock prices in food and beverage companies for the 2016-2020 period